The concept and model of Electronic Document Management System (EDMS) in FTMSK UiTM Shah Alam / Abdul Kadir Mohd Afkar - Mohd Afkar, Abdul Kadir (2005)
Producing documents using computer supported methods has become common practice in the education sector, but the management of documents is still to a large degree done with manual methods. Some pioneering users in university, college and education sectors respectively have applied electronic document management (EDM) within their organizations. However, the introduction has hitherto been noticeably slow. This thesis explains the document analysis process including the processes involve in the workflow of the documents as well as roles who exploit and deal with the documents as the first step in implementing EDM system. The business managements and operations within the Faculty of Information Technology & Quantitative Science been categorized into 5-fold classification respectively. The thesis also discusses the benefits and effectiveness of EDM system to the faculty. The main themes for EDM in the faculty are therefore how to manage the change of information and the exchange or sharing of information between the different users. Two cases of document management in practice have been studied with the processes, documents and roles involve in managing and dealing with it. The overall result of the research provides the business managements and operations within FTMSK and its categories correspondingly. Several reconunendations have been suggested as guidelines and further actions to be taken in order to implement EDM system in the future for the FTMSK